Knowledge, Attitude, and Preventive Behavior Related to Covid-19, Associated Factors And Impact of Information Exposure and Beliefs among College Students: A Review (Journal of Pharmaceutical Negative Results, 2022)
Background:- The highly contagious zoonotic coronavirus (SARS-COV-2) spread to most parts of the world and created a public health emergency in almost 200 countries. Many sources of information and suggestions were developed to guide the public about its transmission and prevent infection. The pathogen responsible for the infection is acute respiratory syndrome coronavirus-2 (SARSCoV-2). The World Health Organization (WHO) made a collaborative effort to tackle the situation and declared it a global pandemic on March 12, 2020. The regularly updated COVID-19 dashboard reported 40, 49, 10,528 confirmed cases and 57, 83,776 deaths globally by this deadly virus by February 12, 2022 (World Health Organization, 2022).In India, COVID-19's first case was reported in Trissur, Kerala, on January 27. A 20-year lady had a history of traveling to China(Andrews MA et al., 2020). Rapid migration of people from the global perspective and between the cities increased the spread of transmission all over the major cities of India. Evidenced-based strategies like social distancing and personal and respiratory hygiene with sustained public cooperation in different countries were mandated to prevent the spread of diseases. The WHO has also issued recommendations for the prevention and control of infection among the general population and healthcare facilities, including hand cleanliness, face masks, social distancing, avoidance of crowds, self-isolation, and immediate medical attention for the person with symptoms of fever, cough, and headache (WHO, 2020).Methods: - An online or web literature review or articles related to Covid-19 and knowledge, attitude, practices, and compliance were conducted through PubMed/Google scholar and BMJ and NIH databases published between Jan 2019 to Jan 2022. Results: - The present review revealed that students' knowledge levels varied from appropriate to high. A positive attitude and acceptable preventive behavior among college students toward Covid-19 were demonstrated. Education level, nationality, habitat, psychological factors, risk perception, health literacy, and early disease awareness were positively associated with knowledge, attitude, and preventive behavior. Those who received most of the information from the World Health Organization, government sources, social media, and TV news channels had good knowledge, positive attitude, and adherence to acceptable preventive behavior. The students with false beliefs and misinformation depicted common knowledge and negative attitude towards COVID-19. Conclusion: - There is a need to convey relevant and updated information through different media access by the student community. Myths and tackling misinformation are substantial as the correct information correlates with increased knowledge, a positive attitude, and more adherence to COVID preventive measures.